2022
DOI: 10.1007/s11150-022-09607-9
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence reporting during the COVID-19 pandemic: evidence from Latin America

Abstract: This article examines changes in the frequency and characteristics of domestic violence reports following the onset of the COVID-19 pandemic and the imposition of mobility restrictions in six Latin American countries. We find significantly different patterns between reports of psychological and physical violence, non-cohabitant and cohabitant violence, and across alternative reporting channels (domestic violence hotlines, emergency lines, and police reports). Calls to domestic violence hotlines soared, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
1
7
0
3
Order By: Relevance
“…U.S. DV incidents were reported to have risen by 8% following stay-at-home orders in 2020; this may be due to factors such as increased unemployment, childcare-related stress, and financial insecurity [ 11 ]. The New York City Police Department reported a similar 10% increase in DV incidents from March 2019 to March 2020 [ 15 ], although police complaints may not accurately capture DV rates during COVID-19 [ 12 ]. In our dataset, the number of domestic violence-related concussions increased from one incident in 2019 to five incidents in 2020.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…U.S. DV incidents were reported to have risen by 8% following stay-at-home orders in 2020; this may be due to factors such as increased unemployment, childcare-related stress, and financial insecurity [ 11 ]. The New York City Police Department reported a similar 10% increase in DV incidents from March 2019 to March 2020 [ 15 ], although police complaints may not accurately capture DV rates during COVID-19 [ 12 ]. In our dataset, the number of domestic violence-related concussions increased from one incident in 2019 to five incidents in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…During the first few months of the COVID-19 pandemic, physicians and providers observed changes in the mechanisms of injury (MOI) for patients and visit volumes. Many studies have examined changes in behavior due to lockdown procedures and their impact on public health secondary to the spread of COVID-19 throughout the world [ 5 , [7] , [8] , [9] , [10] , [11] , [12] , [13] ]. In the first half of 2020, there was an overall decline in physical activity in children, especially for those who lived in apartments and urban areas [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are many studies which point to different patterns in the reporting of domestic violence in the Latin American and Caribbean (LAC) region ( De Souza Santos et al, 2022 ; Ortega Pacheco & Martínez Rudas, 2021 ). However, one study reported an increase in the reporting of this social problem in countries such as Argentina (+62%), Colombia (+98%) and Peru (+39%) with the onset of lockdown ( Perez-Vincent & Carreras, 2022 ). Due to the increase in reported cases of domestic violence, governmental institutions in Mexico, Colombia, Argentina, Brazil, Ecuador and Chile created online and telephone strategies to report domestic violence and reduce its impact ( Lima, 2020 ; Perez-Vincent & Carreras, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…These changes may have resulted in significant modifications in family and marital relationships, with some reports suggesting that the COVID-19 pandemic had a negative impact on satisfaction with family relationships 5 . There are also reports of increased family violence 6,7 . Negative effects on family relationships have also been reported because of the telecommuting being conducted in many countries 2,8 …”
mentioning
confidence: 99%
“…5 There are also reports of increased family violence. 6,7 Negative effects on family relationships have also been reported because of the telecommuting being conducted in many countries. 2,8 Significant external stress events such as disasters have different effects on family relationships depending on the nature of the event, such as the severity of the impact on life and health, the duration of the impact, and the geographic extent of the impact.…”
mentioning
confidence: 99%